Analisis Implementasi Kebijakan Pengelolaan Sarana dan Prasarana Sekolah Di SMP Negeri 2 Batu - Tanggela, Martinus (Program Studi Magister Pedagogi, 2013)
The trend of thinking about education suggests that, educational paradigm based on standards were discussed more and more, acknowledged and appreciated. This trend started from the realization that education need a reference of quality for each of the organizers and the educational unit which is called the National Education Standards (SNP). Indicator of education quality obtained through the filled based on eight ational Education Standards (SNP). Management of facilities and infrastructure were declare based on policy from Permendiknas No.19 in 2007. Based on the previous research has found many gaps related with this context. However, there was no studies have evaluated the mechanism of facilities and infrastructure as a whole and systematically according to grant theory. These mechanisms include the supply, distribution, use and maintenance, inventory, and elimination of school facilities and infrastructure (Bafadal, 2008:7). The purpose of this paper: (1) to describe the implementation of procurement policy and the distribution of school facilities and infrastructure in SMP Negeri 2 Batu, (2) to describe the use of policy implementation and maintenance of school facilities and infrastructure in SMP Negeri 2 Batu, and (3) to describe the implementation of policies inventory and the elimination of school facilities and infrastructure in SMP Negeri 2 Batu.